Proactive Personality dan Innovative Work Behavior : Peran Mediasi Work Engagement - Mokhammad Khukaim Barkhowa; Slamet Mukhamim (Jurnal Ekonomika dan Bisnis, 2023)
Tridharma is the University's commitment to providing education, research, and community service. Then, all of the lecturer's duties and obligations constitute the lecturer's workload (BKD). Looking at the data in the Science and Technology Index, Central Java still needs to improve in terms of publications. In Salatiga City, only one University in the Higher Education Clusterization Announcement with number 0183/E5.5/AL.04/2023, 8 March 2023, was included in the clusterization. Innovative work behavior, work engagement, and proactive personality are one way to contribute to organizational progress and increase the functional position of lecturers. This scientific study was carried out by lecturers in Salatiga City based on the Salatiga City Central Statistics Agency, totaling 833 people. Due to limitations, sampling was carried out in this study using calculations using the Slovin formula with a sample size of 90 lecturers. The sample citing method uses a probabilistic sampling method, namely a sample citing method that equalizes the probability that each element (member) of the population will be selected as a member of the sample. Sampling uses simple random sampling, namely sampling, and population members are taken randomly without controlling the layers in the population. The data analysis technique to answer this research hypothesis uses the Smart Partial Least Square (PLS) tool. The results of this research show that proactive personality statistically has a positive and significant effect on innovative work behavior, proactive personality has a statistically positive and significant effect on work engagement, work engagement has a statistically positive and significant effect on innovative work behavior, and proactive personality has a statistically positive and significant effect on the significant impact on innovative work behavior mediated by work engagement.